RESTRUKTURISASI KREDIT DAN KECUKUPAN MODAL DALAM MEMPENGARUHI LIKUIDITAS PERBANKAN DENGAN DIMODERASI BANK SIZE - Cindy Mariani, (2023)
Since the onset of the COVID-19 pandemic, it is known that financial ratios in banking financial reports have continued to experience changes which have caused various problems. The purpose of this study is to find out how the effect of credit restructuring and capital adequacy on bank liquidity is moderated by bank size. The samples chosen in this study are Conventional Commercial Banks and Sharia Commercial Banks registered with the Financial Services Authority (OJK) in 2020-2021. The technique used in determining the number of samples is a purposive sampling method and produces as many as 61 banks which are the number of samples. Testing the hypothesis in this study using Multiple Linear Regression Analysis with the STATA program and a significance level of 5% (0.05). The test results show that credit restructuring has a significant negative effect on banking liquidity, capital adequacy has a significant positive effect on banking liquidity, bank size can moderate the effect of credit restructuring on banking liquidity, and bank size cannot moderate the effect of capital adequacy on banking liquidity.